Pathogenesis, diagnosis and management of diabetic foot ulcers: a systematic review - Panchakshari, Madhuri K.; Patel, Nilesh J.; Thakkar, Nimesh B.; Patel, Kenil Kirit (International Journal of Research in Medical Sciences, 2022)
Diabetic foot ulcers lead to substantial morbidity and impair quality of life with high treatment costs and enormous economic losses. Diabetic foot ulcers readily become chronic; all too often these wounds do not heal primarily. Treatment of chronic wounds should be essentially directed against the main etiologic factors responsible for the wound. There are different treatment approaches for wound healing in diabetic foot ulcers. If treatment is based on the pathological cause, it may give better results and it must be cost effective too. Hydrogel dressing, platelet rich plasma, placenta extract gel, vacuum dressing are newer modalities in diabetic foot management.